Bicuspid Aortic Valve Stenosis: From Pathophysiological Mechanism, Imaging Diagnosis, to Clinical Treatment Methods - Perrin, Nils; Ibrahim, Réda; Dürrleman, Nicolas; Basmadjian, Arsène; Leroux, Lionel; Demers, Philippe; Modine, Thomas; Ben Ali, Walid (Frontiers in Cardiovascular Medicine, 2022)
Bicuspid aortic valve (BAV) is the most frequent congenital anomaly and has a natural evolution towards aortic regurgitation or stenosis due to the asymmetrical valve function associated to an evolutive ascending aortopathy. Several BAV classifications exist describing presence and number of raphe, amount and location of calcium as well as symmetry of the functional cusps. Impact of BAV morphology on TAVI outcomes still remains little investigated. Pivotal randomized trials comparing transcatheter aortic valve implantation (TAVI) to surgery have excluded BAV until yet. However, data from registries and observational studies including highly selected patients have shown promising results of TAVI in BAV. With this review, we aimed at describing anatomical and pathophysiological characteristics of BAV, discussing the main aspects to assess with diagnostic imaging modalities, and giving an overview of TAVI outcomes and technical considerations specific to BAV morphology.